Cognitive Distortions in Men Who Have Exited White Supremacist Groups - Munden, Hanna Paalgard (Terrorism and political violence, 2025)
Despite reports of longterm cognitive and emotional difficulties after exiting right-wing extremist groups, the latter stages of the extremist group member’s trajectory have been given little attention.1 This paper argues that clinical psychological theory has been underutilised in terrorism and extremism research in general, and, more specifically, that it can make a significant contribution to the understanding of the development and maintenance of unhelpful thinking that can hamper and prolong the reintegration process. The empirical data presented consists of sixteen life-history interviews and one group interview with three men who were former members of white supremacist groups. By applying codebook thematic analysis, five automatic cognitive distortions that developed during group membership and persisted after leaving were identified. These distortions offer a clinical explanation for the unwanted negative and automatic group-related cognitions and concomitant emotions that continue long after leaving. It is argued that CVE interventions should be informed by a recognition of the ways in which cognitive distortions can negatively affect the exit process.